Renal epithelial sodium channel is critical for blood pressure maintenance and sodium balance in the normal late pregnant rat. Issue 5 (28th March 2014) - West, Crystal A.; Han, Weiquing; Li, Ningjun; Masilamani, Shyama M. E.
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Normal pregnancy is a state marked by avid sodium retention and plasma volume expansion. Increased epithelial sodium channel (ENaC) activity in pregnancy may mediate these changes. We investigated the role of the ENaC using pharmacological and genetic inhibition. What is the main finding and its importance? We found that chronic ENaC blockade (systemic and local renal) prevented normal sodium retention in the pregnant rat. Prevention of sodium retention was associated with a decrease in maternal blood pressure and body weight, as well as fetal growth restriction. Taken together, these findings emphasize the importance of increased ENaC activity during pregnancy in maintaining the pregnancy‐mediated changes in sodium balance, volume status and blood pressure. Normal pregnancy is a state marked by avid sodium retention and plasma volume expansion. Insufficient plasma volume expansion results in the compromised maternal state of intrauterine growth restriction, which afflicts ∼5% of all human pregnancies. We have recently shown that renal epithelial sodium channel (ENaC) activity in vivo in the late pregnant (LP) rat is increased. To determine the importance of the renal versus extrarenal ENaC in sodium retention and blood pressure regulation during pregnancy, we have chronically blocked the ENaC pharmacologically with daily subcutaneous injections of benzamil and genetically using intrarenal transfection of αENaC short hairpin RNA. Compared with untreated LP control animals, LP rats treated with benzamil retain less sodium and have reduced mean arterial blood pressure. Furthermore, LP rats treated with benzamil had lower maternal body weight gain. Intrarenal transfection of αENaC short hairpin RNA versus scrambled small RNA successfully decreased renal αENaC mRNA expression in LP rats. Intrarenal transfection of αENaC short hairpin RNA reduced maternal sodium retention, body weight gain and pup weight. Redundant physiological systems that protect blood pressure and sodium homeostasis were unable to compensate for the loss of ENaC activity in the pregnant rat. These findings demonstrate that the renal ENaC is necessary for maintaining pregnancy‐mediated sodium retention, volume expansion and blood pressure regulation.